20 Years of the Research Center for Children’s Health: Results and Development Prospects (Speach at the meeting of the Academic Council on 14 September 2018) - Alexander A. Baranov (Вопросы современной педиатрии)
The article is devoted to the 20th anniversary of the establishment of the Research Center for Children’s Health — an institution with a long history, rich in scientific and practical achievements in the field of children’s health. By the time of receiving a new status, the Center was in a difficult material and technical condition that did not allow it to perform its inherent function of the leading pediatric institution of the country. Owing to the institution management together with a highly professional team and the support of the founders, the Center was provided with modern diagnostic equipment in a short time, new units were opened, numerous fundamental and applied research was carried out, new national clinical guidelines were developed for the treatment of childhood diseases, which allowed the Center to reach the international level.